2015 AIChE Spring Meeting & 11th Global Congress on Process Safety : 30th Center for Chemical Process Safety International Conference (CCPS) (Center for Chemical Process Safety/AIChE, 2015)
This book is one of four parallel symposia that comprise The Global Congress on Process Safety (GCPS). Organized by volunteers from industry and academia, the CCPS conference promotes process safety by identifying emerging process safety issues and advancing leading process safety management practices. The final conference agenda will consist of nine sessions, each with at least 25-minutes presentations. -- Provided by publisher.
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books